Penerapan Metode MDLC dalam Pembuatan Animasi 3D Islami “Cahaya di Kegelapan” Menggunakan Blender - Diana, Nirma Nur (Maliki Interdisciplinary Journal, 2026)
In today's digital era, animation has become one of the most effective media for conveying information, whether for entertainment, education, or religious outreach (dakwah). This study aims to produce an Islamic-themed 3D animation titled "Light in the Darkness", which highlights the moral value of the importance of prayer and how Allah provides guidance to humans in facing fear. The animation was developed using the Multimedia Development Life Cycle (MDLC) method, which consists of six stages: concept, design, material collecting, assembly, testing, and distribution. In the animating stage, the Pose to Pose method was applied to produce expressive and efficient character movements. The production process was carried out using Blender software, starting from character modeling, rigging, and animation, to rendering. The final result of this project is a ±1-minute 3D animation that successfully serves as an engaging and easily understood medium for dakwah, particularly among students and the general public. The use of the Pose to Pose method proved effective in producing natural character movements with proper timing and spacing, while maintaining production time efficiency. This animation conveys the moral message that even in the most difficult situations, Allah always provides light and guidance to those who pray sincerely.